Outcomes of adjuvant radiation therapy after chemotherapy in resected extrahepatic cholangiocarcinoma: A National Cancer Database analysis. Issue 6 (21st December 2022) - Shridhar, Ravi; Blinn, Paige; Huston, Jamie; Meredith, Kenneth L.
Abstract: Background: Adjuvant capecitabine is considered a standard of care for resected cholangiocarcinoma per the BILCAP trial. The role of adjuvant radiation therapy in that trial was not addressed. This study was designed to examine the outcomes of adjuvant radiation in patients who received chemotherapy for resected cholangiocarcinoma. Methods: Using the National Cancer Database, the authors identified high‐risk patients with resected extrahepatic cholangiocarcinoma with either positive nodes (N+) or margins (R1) who received adjuvant chemotherapy between 2006 and 2014. Overall survival (OS) was determined with the Kaplan–Meier method. Propensity score matching (PSM) and multivariate analysis (MVA) were performed to identify prognostic factors for survival. Results: The authors identified 1478 patients after PSM who were included in the analysis. There was no difference in OS between patients receiving single‐agent chemotherapy and patients receiving multiagent chemotherapy ( p  = .69). There was a significant OS benefit associated with radiation therapy. The median OS and the 5‐year OS rate for radiated patients versus nonradiated patients were 34 months and 33% versus 27 months and 24% ( p  < .001) for the whole group, 30 months and 29% versus 24 months and 19% ( p  = .007) for the N+ subgroup, and 25 months and 23% versus 20 months and 12% ( p  = .03) for the R1 subgroup. MVA demonstrated that age, N stage, T stage, R1, and grade were associated with increased mortality, whereas adjuvant radiation was associated with decreased mortality ( p  < .001). Conclusions: This is the first study showing that adjuvant radiation therapy after chemotherapy resulted in a significant OS benefit for patients with resected high‐risk extrahepatic cholangiocarcinoma. Trials are needed to address the role of radiation therapy in this population. Abstract : This study shows that adjuvant radiation therapy after chemotherapy results in a significant overall survival benefit for patients with resected high‐risk extrahepatic cholangiocarcinoma.